Europejskie wpływy na funkcjonowanie samorządu terytorialnego w Polsce - Korczak, Jerzy (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
This article presents the implications of EU accession and ratifi cation of European laws for the regime and principles of functioning of local government. The analysis is carried out in selected local government activity levels and is based on the schema listings together European law and European Union and national law with simultaneous assessment of its outcome.
Keywords: europeanisation of administrative law; local government; right to good administration; transparency of activity; regional development